Reassessing intertemporal choice: human decision-making is more optimal in a foraging task than in a self-control task - Carter, Evan C.; Pedersen, Eric J.; McCullough, Michael E. (Frontiers in Psychology, 2015)
Many contemporary concerns (e.g., addiction, failure to save) can be viewed as intertemporal choice problems in which the consequences of choices are realized at different times. In some laboratory paradigms used to study intertemporal choice, non-human animals demonstrate a preference for immediacy (impulsive choice) that results in failures to maximize the amount of reward received. There is evidence, however, suggesting that such non-optimal impulsive choice may be due to a mismatch between the standard presentation of options in the laboratory (e.g., a “larger-later” and a “smaller-sooner” option) and the way that options occur in natural settings (e.g., foraging). We present evidence that human impulsive choice is similarly affected: In two experiments, decisions were more optimal when options were presented in a format sharing features with the evolutionarily important problem of foraging compared to when options were presented in the standard format. These findings suggest a more nuanced view of intertemporal choice and support the adoption of ideas from foraging theory into the study of human decision making.